The Impact of Organizational Citizenship Behaviour on Innovation Performance of Employees in Chinese Small and Medium-Sized Enterprises - Li Zhao; Khaw, Khai Wah; Xinying Chew; Sharon Peck Yeng Cheang (Journal of Technology Management and Business, 2024)
In the rapidly evolving economic landscape of China, Small and Medium-sized Enterprises (SMEs) have emerged as pivotal players, driving growth and fostering innovation. However, the dynamics of Organizational Citizenship Behaviour (OCB) and job satisfaction within these enterprises, and their subsequent influence on an employee's innovative performance, remain underexplored. By focusing on the interplay between OCB, job satisfaction, and innovative performance within Chinese SMEs, this research aims to bridge the existing knowledge gap and provide valuable insights for both academia and industry practitioners, During the test phase, a total of 412 questionnaires were disseminated to respondents of SMEs, using PLS-SEM as an instrument to analyze statistics, the result showed that organizational citizenship behaviour has an important influence on SMEs employees innovation performance.